Grind hardening process - Salonitis, Konstantinos (Springer International Publishing, 2015)
Presents the grind-hardening process and the main studies published since it was introduced in 1990s. The modelling of the various aspects of the process, such as the process forces, temperature profile developed, hardness profiles, residual stresses etc. are described in detail. The book is of interest to the research community working with mathematical modeling and optimization of manufacturing processes.